Noninvasive Vascular Diagnosis A Practical Textbook for Clinicians - AbuRahma, Ali F.; Perler, Bruce A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This revised and updated edition reflects the increasing popularity of noninvasive techniques in the management of vascular disease. It represents the definitive text written on the subject and has been honed over the past editions to represent the enormous number of changes to the use of imaging to diagnose the multitude of conditions being seen in the clinic and surgical suite. Noninvasive Vascular Diagnosis comprehensively covers all aspects of noninvasive evaluation of the circulatory system, including the extremities, cerebrovascular, and abdomen. In this updated edition, it is well supported by exceptional illustrative material, making it invaluable to all those who work in vascular laboratories as well as internists, cardiologists, radiologists, vascular surgeons, vascular medicine specialists, vascular laboratory directors and staff, general surgeons involved in vascular surgery and the vascular surgery community in general.
Part I Vascular Laboratory Operations -- Improving Quality in Noninvasive Testing by Certification and Accreditation -- Physician Qualifications in the Clinical Diagnostic Vascular Laboratory -- Quality in the Vascular Laboratory -- Ergonomics and Vascular Lab -- Part II Vascular Hemodynamics and Basic Vascular Physics -- Principles of Vascular Ultrasound Physics -- Vascular Hemodynamics -- Part III Noninvasive Diagnosis of Cerebrovascular Disease -- Overview of Cerebrovascular Disease -- Color Duplex Scanning of the Extracranial Carotid Arteries -- Ultrasonic Characterization of Carotid Plaques and Its Clinical Implications -- Role of Duplex Ultrasound in Carotid Screening -- Duplex Ultrasound Velocity Criteria in Carotid Artery Stenting Patients -- Intraoperative Ultrasound Assessment of Carotid Endarterectomy and Carotid Stent Angioplasty -- Intima-Media Thickness and Plaque Evaluation: Predictive Value of Cardiovascular Events and Contribution to Cardiovascular Risk Evaluation -- Color Duplex Scanning of the Brachiocephalic/Subclavian Arteries -- Color Duplex Scanning of Vertebral Artery -- Transcranial Doppler Sonography -- TCD Monitoring During Carotid Artery Stenting -- Errors and Artifacts of Carotid Ultrasound Evaluation -- Computed Tomography Angiography and Magnetic Resonance Angiography of the Carotids -- Carotid Duplex Consensus Criteria on Interpretation of Carotid Duplex Ultrasound -- Correlation of Doppler PSV/EDV in Determining Severity of Stenosis Beyond 70%: 70-80%, 80-90% and >90% -- Role of Duplex Ultrasound in Subclavian Steal: Incidence and Clinical Implications -- Duplex Ultrasound Surveillance After Carotid Endarterectomy -- Color Duplex Scanning on Other Miscellaneous Carotid Topics -- Part IV Noninvasive Diagnosis of Peripheral Arterial Disease of the Extremities -- Overview of Peripheral Arterial Disease of the Lower Extremity -- Segmental Doppler Pressures and Doppler Waveform Analysis in Peripheral Vascular Disease of the Lower Extremities -- Pulse Volume Recording in the Diagnosis of Peripheral Vascular Disease -- Duplex Ultrasound Assessment of Lower Extremity Arterial Disease -- Duplex Surveillance of Infrainguinal Bypass Grafts -- Duplex Surveillance After Prosthetic Infrainguinal Bypass Grafting -- Rationale of Surveillance After Endovascular Intervention of Iliac and Femoral Arteries -- Lower Extremity Arterial Mapping: Duplex Ultrasound as an Alternative to Arteriography Prior to Femoral, Popliteal, and Infrapopliteal Reconstructions -- Duplex Ultrasound: Evaluation and Management of Post-catheterization Femoral Pseudoaneurysms -- Noninvasive Diagnosis of Upper Extremity Arterial Disease -- Duplex Ultrasound Imaging of the Radial Artery -- Vascular Laboratory Protocol and Ultrasound Mapping Techniques for Dialysis Access Planning -- Color Duplex Ultrasound in Dialysis Access Surveillance -- Noninvasive Evaluation for Congenital Arteriovenous Fistulas and Malformations -- Noninvasive Vascular Testing in the Trauma Patient -- Color Duplex Ultrasound for Diagnosis of Peripheral Artery Aneurysms -- Color Duplex Ultrasound in Other Miscellaneous Arterial Topics -- Part V Noninvasive Diagnosis of Venous Disorders of the Extremities -- Overview of Venous Disorders -- Plethysmographic Techniques in the Diagnosis of Venous Disease -- Color Venous Duplex Ultrasound of the Lower Extremity in the Diagnosis of Deep Venous Thrombosis -- Color Duplex for Diagnosis of Venous Reflux -- Venous Duplex Ultrasound of the Upper Extremities -- Role of the Noninvasive Vascular Laboratory in Thoracic Outlet Syndrome -- Color Duplex Ultrasound-Guided Cava Filter Placement -- Intravascular Ultrasound for Venous Stenting and Inferior Vena Cava Filter Insertion -- The Role of Duplex Ultrasound Before, During, and After Endovenous Procedures -- Preoperative Saphenous Vein Mapping -- Role of Follow-Up Duplex Ultrasound Post Deep Vein Thrombosis -- Role of Duplex Ultrasound Screening/Surveillance in High-Risk Deep Vein Thrombosis Patients -- Part VI Noninvasive Diagnosis of Abdominal/Visceral Arteries -- Color Duplex Scanning of the Hepatoportal Circulation -- Color Duplex Scanning of the Renal Arteries -- Duplex Ultrasound of Renal Transplants -- Duplex Evaluation After Renal Artery Intervention -- Duplex Ultrasonography of the Mesenteric Circulation -- Color Duplex Scanning of Superior Mesenteric and Celiac Artery Stenting -- The Role of Color Duplex Ultrasound in Patients with Abdominal Aortic Aneurysms and Peripheral Aneurysms -- Clinical Validation of 3-Dimensional Ultrasound for Diagnosis of Abdominal Aortic Aneurysm -- Duplex Ultrasound Screening for Abdominal Aortic Aneurysm -- Role of Color Duplex Ultrasound for Aortic Endografts -- Role of CT Angiography in Pre and Post Abdominal Aortic Aneurysm Endovascular Grafts -- Part VII Miscellaneous -- Transcutaneous Oxygen Tension: Principles and Applications -- Three-Dimensional Vascular Imaging and Power Doppler Angiographic Imaging -- Contrast-Enhanced Ultrasound -- Arterial and Venous Intravascular Ultrasound Applications -- Coding and Reimbursement for Vascular Lab Testing -- Clinical Application of Ultrasound Guidance in Arterial and Venous Access -- Computed Tomographic Angiography in the Diagnosis of Peripheral Arterial Disease -- Magnetic Resonance Angiography in the Diagnosis of Peripheral Arterial Disease -- Role of Vascular Laboratory in Society for Vascular Surgery Vascular Center Certification.
Keywords: Radiology; Cardiology; Internal medicine; Surgery; Radiology; Cardiology; Internal Medicine; Surgery; Cerebrovascular Disorders -- diagnosis; Endovascular Procedures